The role of local embeddedness of transnational migrant start-ups in the COVID-19 crises: Examples from the Berlin start-up ecosystem - Judith Terstriep; Alexandra David; Alexander Ruthemeier; Maria Elo (Institut Arbeit und Technik (IAT), 2022)
The COVID-19 pandemic has led to a changing environment for transnational migrant start-ups. These changes have posed many challenges concerning altering strategic behaviour and approaches to driving business. We explored transnational migrant start-ups' embeddedness in translocal entrepreneurial ecosystems by analysing data from 14 semi-structured interviews with start-ups from Berlin's knowledgeintensive business services sector. We argue that the success of transnational migrant start-ups during crises is largely dependent on embeddedness in the local entrepreneurial ecosystem. Thus, we expect entrepreneurs to utilise local networks, infrastructures and interactions to help them cope with the challenges at hand and to pave the way for translocal business activities. Our results indicate that structural embedding in local entrepreneurial ecosystems and a sense of belonging, especially during the business formation phase, play a vital role for transnational migrant start-ups.
Keywords: F63; O12; L26; 330; migrant entrepreneurship; migrant start-ups transnationalism; translocal embeddedness; COVID-19; crisis; entrepreneurial ecosystem